Preparation of chemically reduced graphene oxide reinforced Epoxy Resins polymer as a composite for electromagnetic interference shielding and microwave absorbing applicationns - Ahmad, Ahmad Fahad; Ab. Aziz, Sidek; Abbas, Zulkifly; Obaiys, Suzan Jabbar; Khamis, Ahmad Mamoun; Hussain, Intesar Razaq; Mohd Zaid, Mohd Hafiz (MDPI, 2018)
The preparation of chemically reduced graphene oxide (rGO) and the optimization of epoxy resins’ properties using micro or nanofillers are now common practices. rGO nanoparticles (60 nm) based on an epoxy resin polymer were prepared at the concentrations of 0, 1, 2, 3, 4, and 5% weight percentage with fixed 6-mm thicknesses. The dielectric properties of the composites were measured by the reflection/transmission technique in connection with a vector network analyser (VNA) at a frequency range of 8–12 GHz. The microwave absorption and shielding effectiveness properties were calculated by using the reflection S₁₁ and transmission S21 results. The microstructure and morphology of the polymer and the rGO/cured epoxy composites were studied by field emission scanning electron microscopy (FE-SEM), Fourier-transform infrared (FT-IR) spectroscopy, and the X-ray Diffraction (X-RD) technique for characterizing crystalline materials. The dielectric and other properties of the rGO/cured epoxy composites were investigated based on the filler load and frequency. It was found that the applied frequency and the filler concentrations affected the dielectric properties of the rGO/cured epoxy composites. The results showed that the introduction of rGO particles to the composites increased their dielectric properties smoothly. The study of the dependence on frequency of both the dielectric constant ε′ and the dielectric loss ε″ showed a decrease in both quantities with increasing frequency, indicating a normal behaviour of the dielectrics. Cole–Cole plots were drawn with ε′ and ε″. A theoretical simulation in terms of the Cole–Cole dispersion law indicates that the Debye relaxation processes in the rGO/cured epoxy composites are improved due to the presence of the rGO filler. Moreover, with the addition of rGO as a filler into the Epoxy matrix, it now exhibits promise as a lightweight material for microwave absorption as well as an effective electromagnetic interference (EMI) shielding material.